PENGEMBANGAN ETANOL SEMI PADAT DENGAN PENCAMPURAN MINYAK JELANTAH - Setiawan, Beny; Restuhadi, Fajar; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to obtain the concentration of sodium hydroxide (NaOH) and the appropriate concetration of ethanol with a mixture of waste cooking oil to formulate the semi-solid ethanol as an alternative for house hold fuel. The research was carried out by using completely randomized design (CRD) with factorial design. The first factor is the concentration of NaOH (12, 13, 14, and 15%), and the second factor is the concentration of ethanol (85, 90, and 95%). Results of analysis of variance showed interaction of ethanol concentration and the addition of NaOH concentration significanly affected the degree of acidity (pH) and the calorific value. The addition of different concentrations of ethanol, significantly affected on burning residue, calorific value, and heat transfer. The addition of different concentrations of NaOH significantly affected on viscosity, acidity (pH), burning residue, calorific value and heat transfer. At the beginning of the burning, flame color changed from blue to yellowish blue,, then to yellow flame before the flame extinguished. The best formulation of semi-solid ethanol is treatment A2B3 whic shows a viscosity of 19,500 cP, the calorific value of 22,519 J/g and 45.34% combustion residues. Keywords: ethanol, NaOH, waste cooking oil, ethanol semi-solid.